Pharmacotherapy for obesity management - Noeth, M; Van Zyl, F H; Hellig, J; Conradie-Smit, M; May, W (South African medical journal, 2025)
RECOMMENDATIONS 1. Pharmacotherapy for obesity management can be used for individuals with a BMI ≥30 kg/m2, or ≥27 kg/m2 with adiposity-related complications, in conjunction with medical nutrition therapy, physical activity and psychological interventions (semaglutide 2.4 mg weekly [Level 1a, Grade A] liraglutide 3.0 mg daily [Level 2a, grade B], naltrexone/bupropion 16 mg/180 mg twice a day [BID] [Level 2a, Grade B], orlistat 120 mg three times a day [TID] [Level 2a, Grade B]). 2. Pharmacotherapy may be used to maintain weight loss and to prevent weight regain (liraglutide 3.0 mg daily [Level 2a, Grade B], orlistat 120 mg TID [Level 2a, Grade B]). 3. Pharmacotherapy for obesity management in conjunction with health behaviour changes for people living with prediabetes and overweight or obesity (BMI ≥27 kg/m2) can be used to delay or prevent T2DM (liraglutide 3.0 mg daily [Level 2a, Grade B], orlistat 120 mg TID [Level 2a, Grade B]). 4. Obesity pharmacotherapy can be used in conjunction with health behaviour changes in people living with T2DM and a BMI ≥27 kg/m2, for weight loss and improvement in glycaemic control (semaglutide 2.4 mg weekly [Level 1a, Grade A], liraglutide 3.0 mg daily [Level 1b, Grade A], naltrexone/bupropion 16 mg/180 mg BID [Level 2a, Grade B], orlistat 120 mg TID [Level 2a, Grade B]). 5. Pharmacotherapy can be considered in conjunction with health behaviour changes in treating people with obstructive sleep apnoea and a BMI ≥30 kg/m2, for weight loss and associated improvement in the apnoea-hypopnoea index (liraglutide 3.0 mg daily [Level 2a, Grade B]). 6. Pharmacotherapy can be considered in conjunction with health behaviour changes in treating people living with metabolic dysfunction- associated steatohepatitis (MASH) and overweight or obesity, for weight loss and improvement of MASH parameters (liraglutide 1.8 mg daily [Level 3; Grade C], semaglutide 2.4 mg [Level 4 Grade D]). 7. Metformin and psychological treatment (such as cognitive behavioural therapy) should be considered for prevention of weight gain in people with severe mental illness who are treated with antipsychotic medications associated with weight gain (Level 1a, Grade A). 8. For people living with overweight or obesity who require pharmacotherapy for other health conditions, we suggest choosing medications that are not associated with weight gain (Level 4, Grade D, Consensus). 9. We do not suggest the use of prescription or over-the-counter medications other than those approved in SA for obesity management (Level 4, Grade D, Consensus).